Redgram Bajra Intercropping Under Semi-Arid Conditions of Anantapur Region of Andhra Pradesh - Reddy, P R; Reddy, Y Rama (Annals of Arid Zone, 2016)
Redgram sown in June recorded significantly higher yield components and yield in redgram/bajra intercropping under semi-arid conditions at Anantapur in Andhra Pradesh. Sole crops of redgram and bajra recorded higher yield components and yields than intercrops. Bajra sown as staggered intercrop between the redgram rows at 60 day delay, recorded very low yields bacause of severe competition from the rcdgram. Intcrcropping systems recorded higher LER than the solc crops. Sole redgram sown in June recorded higher monctary returns.